Metastatic Colorectal Cancer: Survival Comparison of Hepatic Resection Versus Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy - Blackham, Aaron U. (2014)
BACKGROUND: Liver resection has long been considered the standard of care for resectable colorectal hepatic metastases (HM). Patients with colorectal peritoneal surface disease (PSD) are now also being treated with aggressive therapy in the form of cytoreductive surgery (CS) and hyperthermic intraperitoneal chemotherapy (HIPEC). METHODS: A retrospective comparison of optimally-treated colorectal cancer patients with HM or PSD obtained from prospectively maintained databases (1991–2010). RESULTS: Liver resection was performed on 179 patients with HM, while 93 PSD patients received a complete cy-toreduction followed by HIPEC. Patients differed in terms of age, performance status, site of primary cancer, T stage, and the use of perioperative chemotherapy. Five-year overall survival for HM patients was 36 %, with a median survival of 46 months, compared with 26 % and 34 months in patients with PSD (p = 0.024). When stratified by resection status, R0 HM (n = 170) and R0 PSD (n = 48) patients had similar median survival (49 vs. 41 months; p = 0.39). Median survival following R1 resection was also similar among HM (n = 9) and PSD (n = 45) patients (28 vs. 23 months; p = 0.68). Multivariate analysis identified distinctly different independent prognostic factors between HM and PSD patients. Major morbidity was 21 and 23 % (p = 0.88), while mortality was 3.9 versus 5.4 % (p = 0.55) in the HM and PSD patients, respectively. CONCLUSION: Colorectal HM and PSD are distinct biologic diseases with different presentations and unique prognostic factors. However, long-term survival following CS/HIPEC is comparable to liver resection when stratified by completeness of resection. Furthermore, perioperative morbidity and mortality are similar.